PENGARUH PANJANG JARING PURSE SEINE DAN JAM KERJA TERHADAP VOLUME PRODUKSI NELAYAN TANGKAP DI KECAMATAN PASARWAJO KABUPATEN BUTON - Muhamad Kaslim Sabaa; La Onu La Ola; Hasnia Arami Arami (UNIVERSITAS HALU OLEO, 2022)
This study aims to: (1) examine the scale of the change in production volume caused by an increase in the length of the net by one unit (2) to examine the scale of the change in the production volume caused by the increase in working hours by one unit (3) to examine the effect of the length of the net and working hours on the production volume of purse seine fishermen in Pasarwajo District. This study uses a case study method with 11 purse seine fishermen as respondents. The process of collecting primary data was carried out by direct observation and interviews using a questionnaire. The primary data collected was the length of the net, hours worked, the amount of production per trip, fuel and consumption. Secondary data was population, education level of fishermen and other data related to this research. The data were analyzed using the Cobb-Douglas function and f-test analysis. The results of the analysis show that: (1) the scale of changes in production volume caused by increasing the length of the net by one unit was 37,777 kg (2) the scale of changes in production volume caused by increasing working hours by one unit was 14,292 kg (3) f-test results obtained that the length of the net and working hours simultaneously have a significant effect on the production volume because the calculated f-value was greater than f-table (155.81 > 8.65 (F.01) 4.46 (F.02))Key words : production volume, net length, working hours